Methods to Test the Compressive Strength of Earth Blocks - Guanqi Lan; Sisi Chao; Yihong Wang; Ying Cui (Advances in Materials Science and Engineering)
The efficient design of new earth structures and the restoration of old structures both require a reliable assessment of the compressive strength of earth materials. However, there is still much debate on the best method to accurately measure the compressive strength of earth blocks. To solve the problem of measuring the compressive strength of the earth block, the cube specimen, the half-block stacked specimen, and the full-size block specimen are used to measure the compressive strength of the molded adobe and rammed adobe, respectively, considering the influence of the specimen preparation process, loading direction, capping, and other factors. By comparing and analyzing the stress state, failure mode, and compressive strength of the specimen under various test methods, a compressive strength test method of earth blocks is determined, which is simple to operate, easy to standardize, and as close as possible to the actual strength of the blocks. The results show that the full-size block compression test method along the block thickness direction should be preferred to test the compressive strength of the earth block. The standard specimen obtained by cutting the full-size block is not suitable for the test of the compressive strength of the earth block; it can effectively solve the problem that the compressive strength of the small-thickness earth block cannot be directly measured by cutting the full-size block in half and stacking it, but it is not recommended to use the binder to bond the two half-blocks. When comparing the compressive strength of the earth blocks, the conversion coefficient related to the height-to-thickness ratio of the specimen cannot be used to convert the compressive strength. Still, the anisotropy of the material strength should be considered.